Analyzing intermediaries that determines purchase behavior of iPad users for digital products within iPadOS applications: consumer study for Lettre.app - Ahmed, Saif (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.